2010
DOI: 10.1007/s11199-010-9910-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization History and Perceived Similarity to a Sexual Assault Victim: A Path Model of Perceiver Variables Predicting Victim Culpability Attributions

Abstract: Extant research consistently has shown that culpability attributions toward sexual assault victims are predicted by perceiver gender, perceived similarity to victims, empathy for victims, and rape myth acceptance. The purpose of the present study was to conceptually organize these predictors, which often have been treated disparately in literature. The present sample was composed of 69 female undergraduate students, recruited from a psychology research pool at a university in the southwestern United States. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 65 publications
(112 reference statements)
4
51
0
3
Order By: Relevance
“…Furthermore, hostile sexism was found not to be related to victim blaming in some studies depicting date rape scenarios (e.g., Pedersen & Strömwall, 2013;Viki & Abrams, 2002). Higher myth acceptance (e.g., Basow & Minieri, 2011;Cohn et al, 2009;Frese et al, 2004;Grubb & Tarn, 2012;Hammond et al, 2011) and lower rape empathy scores (e.g., Miller et al, 2011;Smith & Frieze, 2003) were suggested to predict increased victim blame.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Furthermore, hostile sexism was found not to be related to victim blaming in some studies depicting date rape scenarios (e.g., Pedersen & Strömwall, 2013;Viki & Abrams, 2002). Higher myth acceptance (e.g., Basow & Minieri, 2011;Cohn et al, 2009;Frese et al, 2004;Grubb & Tarn, 2012;Hammond et al, 2011) and lower rape empathy scores (e.g., Miller et al, 2011;Smith & Frieze, 2003) were suggested to predict increased victim blame.…”
Section: Resultsmentioning
confidence: 90%
“…With reference to the relationship among the four variables under review and victim blaming, most of the literature suggests that gender may predict victim blaming and that this relation is mediated by the degree of rape myth acceptance (e.g., Hammond et al, 2011;Miller et al, 2011). The defensive attributions based on the perceived similarity to a target (Shaver, 1970) may also promote these gendered differences in rape victim blaming, since women may assume themselves as more similar to the victim, hence assigning less blame; this relationship between defensive attribution and victim blaming may be mediated by empathy, as suggested by Shaver (1970).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations